2007
DOI: 10.1002/cncr.22565
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cerebral metastases and neurological death after pathological complete response to neoadjuvant therapy for locally advanced nonsmall‐cell lung cancer

Abstract: BACKGROUND. The incidence and pattern of brain metastases was analyzed among patients who achieved a pathological complete response (pCR) after neoadjuvant chemotherapy or chemoradiotherapy for locally advanced nonsmall‐cell lung cancer (NSCLC). METHODS. Between 1990 and 2004, 211 patients were treated with neoadjuvant therapy before surgical resection for stage III NSCLC. The clinical course of 51 patients who demonstrated a pCR were reviewed. The neoadjuvant regimen consisted of either chemotherapy (29 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 34 publications
5
100
0
2
Order By: Relevance
“…As known, EGFR mutations, being deemed to be a biological marker of NSCLC in recent decades, account for 10%‐25% of NSCLC 53. As a result of its constitutive activation of EGFR signaling and oncogenic transformation, EGFR was confirmed to be an independent risk factor and served as a crucial role 54.…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%
“…As known, EGFR mutations, being deemed to be a biological marker of NSCLC in recent decades, account for 10%‐25% of NSCLC 53. As a result of its constitutive activation of EGFR signaling and oncogenic transformation, EGFR was confirmed to be an independent risk factor and served as a crucial role 54.…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%
“…Although several clinical and pathologic factors have been associated with the development of brain metastases in locally advanced disease, [31][32][33][34][35] few studies have evaluated risk factors in early stage disease (Table 3). On multivariate analysis, we identified 4 factors that were independently associated with a higher risk of developing brain metastases.…”
Section: Clinical and Pathologic Risk Factorsmentioning
confidence: 99%
“…Whereas several other series found a similar finding, 7,31,36 age in other series was not prognostic. 33,34,37 Tumor size is an important prognostic factor in NSCLC and a primary basis for the TNM staging system. 15 Bajard et al showed that clinical T classification was significant for development of brain metastases in a cohort of 305 NSCLC patients (168 with stage I-II disease).…”
Section: Clinical and Pathologic Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations